Interferon regulatory factor 1 (IRF-1) promotes intestinal group 3 innate lymphoid responses during Citrobacter rodentium infection - Schmalzl, Angelika; Leupold, Tamara; Kreiß, Lucas; Waldner, Maximilian; Schürmann, Sebastian; Neurath, Markus; Becker, Christoph; Wirtz, Stefan (Nature Communications, 2022)
Group 3 innate lymphoid cells (ILC3s) are crucial mediators of immunity and epithelial barrier function during immune responses against extracellular bacteria. Here, we identify Interferon regulatory factor 1 (IRF-1), a transcription factor previously associated with type 1 immunity, as an essential regulator of intestinal ILC3 accumulation and effector cytokine production. We demonstrate that IRF-1 is upregulated in the context of infection with the enteropathogen Citrobacter rodentium and that its presence is central for anatomical containment and prevention of pathogen dissemination. We furthermore show that IRF-1 is required in order for intestinal ILC3s to produce large amounts of the protective effector cytokine IL-22 early in the course of infection. On a molecular level, our data indicate that IRF-1 controls ILC3 numbers and their activation by direct transcriptional regulation of the IL-12Rβ1 chain, thereby allowing ILCs to physiologically respond to IL-23 stimulation.
CRIS-Team Scopus Importer:2022-10-14